Building Resilience in Rural STEM Teachers Through a Noyce Professional Learning Community - Sharon S. Vestal; Robert S. Burke; Larry M. Browning; Laura Hasselquist; Patrick D. Hales; Matthew L. Miller; Madhav P. Nepal; P. Troy White (Education Sciences)
Addressing the critical STEM teachers’ shortage in the rural United States requires not only recruiting new teachers but also improving retention and teacher resiliency. This study explores contextual protective factors through the Early Career Teacher Resilience (ECTR) framework. The major objective of this study was to evaluate the impacts of the NSF Noyce Professional Learning Community (PLC) on rural STEM teacher resilience. Key components of the Noyce PLC included scholarship support, pre-service mentoring, attendance at local and regional educational events, active engagement in the program’s annual summer conference, and participation in a closed Facebook group. We developed an ECTR framework-based online instrument with 28 questions and sent it to 311 university alumni, including 44 Noyce alumni. The results suggest that the Noyce PLC has excelled in fostering collaborative learning environments, providing resources that enhance teaching and learning, accommodating new and different ways of thinking, and supporting teachers’ professional growth beyond graduation. The findings underscore the importance of integrating theoretical and practical knowledge, supporting ongoing professional learning, and building strong professional relationships. Several aspects of the Noyce PLC could be replicated in other STEM teacher preparation programs to enhance teacher resilience, effectiveness, and career development.